Development of an innovative sandwich plate for trough‐type railway bridges: Extremely slender deck slab structure in steel‐concrete composite design with cellular longitudinal shear connectors. Issue 3 (August 2016) - Steurer, Marlene; Petraschek, Thomas; Fink, Josef
Abstract: Substitute structures for old railway bridges with open railway tracks, which are constructed in accordance with valid European standards and regulations, require a specific, suitable deck slab design. Therefore, a composite plate with cellular longitudinal shear connectors and a low overall depth of 200 mm has been investigated at the Research Centre of Steel Structures (TU Wien). The research programme comprised experimental studies as well as additional numerical analyses by means of the finite element method concerning the shear force transmission‐mechanism of the sandwich design. Laboratory studies included, among other issues, information about the failure mechanism in the core concrete. This article provides a description of the test program and gives a brief summary of selected research results. A short overview on continuing research activities to determine the serviceability, the load‐bearing capacity as well as the fatigue strength of the sandwich plate is presented.